Daphne's book - "Hahn, Mary Downing." (New York)
"As author Jessica and artist Daphne collaborate on a picture book for a seventh-grade English class contest, Jessica becomes aware of conditions in Daphne's home life that seem to threaten her health and safety."
Keywords: SCHOOLS -- FICTION.;BOOKS AND READING -- FICTION.;AUTHORSHIP -- FICTION.;FAMILY PROBLEMS -- FICTION